2020
DOI: 10.1016/j.bbih.2020.100063
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasma B vitamins in depression and the therapeutic response to electroconvulsive therapy

Abstract: A growing body of research has indicated a role for B vitamins in depression, with some previous studies suggesting that B vitamin status in patients with depression can impact on antidepressant response. Here we aimed to investigate B vitamin plasma concentrations in medicated patients with depression ( n ​= ​94) compared to age- and sex-matched healthy controls ( n ​= ​57), and in patients with depression after electroconvulsive therapy (ECT) in a real-world clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…We employed MESH terms and keywords (all shown in ESF, Table 1) to perform the initial search process, including inspection of 10861 articles. Based on our exclusion criteria 35 studies were selected as eligible in our systematic review and meta-analysis (Cowen, Parry-Billings et al 1989, Anderson, Parry-Billings et al 1990, Maes, Jacobs et al 1990, Price, Charney et al 1991, Quintana 1992, Maes, Meltzer et al 1993, Møller 1993, Maes, De Backer et al 1995, Maes, Wauters et al 1996, Song, Lin et al 1998, Hoekstra, Fekkes et al 2006, Miller, Llenos et al 2006, Myint, Kim et al 2007, Myint, Kim et al 2007, Gabbay, Klein et al 2010, Steiner, Walter et al 2011, Sublette, Galfalvy et al 2011, Erhardt, Lim et al 2013, Bay-Richter, Linderholm et al 2015, Bradley, Case et al 2015, Busse, Busse et al 2015, Dahl, Andreassen et al 2015, Savitz, Drevets et al 2015, Brundin, Sellgren et al 2016, Clark, Pocivavsek et al 2016, Zhou, Zheng et al 2018, Aarsland, Leskauskaite et al 2019, Pompili, Lionetto et al 2019, Sellgren, Gracias et al 2019, Achtyes, Keaton et al 2020, Ryan, Allers et al 2020, van den Ameele, van Nuijs et al 2020, Milaneschi, Allers et al 2021, Trepci, Sellgren et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We employed MESH terms and keywords (all shown in ESF, Table 1) to perform the initial search process, including inspection of 10861 articles. Based on our exclusion criteria 35 studies were selected as eligible in our systematic review and meta-analysis (Cowen, Parry-Billings et al 1989, Anderson, Parry-Billings et al 1990, Maes, Jacobs et al 1990, Price, Charney et al 1991, Quintana 1992, Maes, Meltzer et al 1993, Møller 1993, Maes, De Backer et al 1995, Maes, Wauters et al 1996, Song, Lin et al 1998, Hoekstra, Fekkes et al 2006, Miller, Llenos et al 2006, Myint, Kim et al 2007, Myint, Kim et al 2007, Gabbay, Klein et al 2010, Steiner, Walter et al 2011, Sublette, Galfalvy et al 2011, Erhardt, Lim et al 2013, Bay-Richter, Linderholm et al 2015, Bradley, Case et al 2015, Busse, Busse et al 2015, Dahl, Andreassen et al 2015, Savitz, Drevets et al 2015, Brundin, Sellgren et al 2016, Clark, Pocivavsek et al 2016, Zhou, Zheng et al 2018, Aarsland, Leskauskaite et al 2019, Pompili, Lionetto et al 2019, Sellgren, Gracias et al 2019, Achtyes, Keaton et al 2020, Ryan, Allers et al 2020, van den Ameele, van Nuijs et al 2020, Milaneschi, Allers et al 2021, Trepci, Sellgren et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…38 included studies recruited humans ( Table 2 ) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] and 27 studied animal models ( Table 3 ) [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ,…”
Section: Resultsmentioning
confidence: 99%
“…We also found dietary vitamin B3 intake was associated with a reduced risk of depression, which also agrees with previous studies (Smesny et al 2010;Thompson and Proctor 1953). In a recent study, it was reported vitamin B3 levels were substantially lower in patients with depression than in controls (Ryan et al 2020). It may be that vitamin B3 is transf o r m e d i n v i v o i n t o n i c o t i n a m i d e , w h i c h h a s benzodiazepine-like effects on the γ-aminobutyric acid (GABA) system (Möhler et al 1979;Tallman et al 1980).…”
Section: Discussionmentioning
confidence: 99%